What is the minimum a doctor should know about health economics? Qual o mínimo que um médico deve entender de economia da saúde? - Philip Musgrove (Instituto Materno Infantil de Pernambuco, 2001)
A doctor need not learn a great deal of economics in order to understand some of the basic ideas of health economics. What is more important than any particular piece of knowledge is to understand how economists think, particularly how and why they think about markets. Health economics emphasizes some market failures which lead to poor health outcomes or high costs or both, and it concentrates especially on issues of how health care is paid for - the sources of funding, the pooling of those funds to provide protection from financial risk, and their use to purchase goods and services. Better understanding between economists and health professionals can reduce incomprehension and antagonism, and offer opportunities for more efficient and equitable health systems. Um médico não precisa saber muito de economia para entender algumas idéias básicas da economia da saúde. Mais importante do que qualquer conhecimento específico, é entender como os economistas pensam, sobretudo como e por quê eles pensam sobre os mercados. A economia da saúde enfatiza certos fracassos de mercado que geram maus resultados em saúde, ou custos altos, ou ambas as coisas. Concentra-se, especialmente, no financiamento da saúde - as fontes de recursos, sua aglomeração para proteger as pessoas contra riscos financeiros, e seu uso para comprar bens e serviços. Um melhor entendimento entre economistas e profissionais médicos pode reduzir incompreensões e antagonismos, como também oferecer oportunidades para sistemas de saúde mais eficientes e mais eqüitativos.